Intellectual Capital, Dividend Policy, Corporate Risk Disclosure And Firm Equity Valuation In Banking Companies Indonesia - Habsyi, Muhamad Anton; Sutisna; Sari, Gema Ika (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The assessment of equity value serves as a crucial indicator in the banking sector, which plays a strategic role in the national economy. Fluctuations in PBV among listed banks on the IDX during 2020–2024 reflect dynamic market perceptions of banking performance. This study investigates the influence of intellectual capital and dividend policy on equity valuation with corporate risk disclosure (CRD) as an intervening variable. A quantitative research design was employed using panel data regression analysis. The sample consists of 20 banking companies listed on IDX for 2020–2024 period, with data processed through EViews software. The findings reveal that intellectual capital exerts a positive effect on equity valuation. Dividend policy and CRD demonstrate no significant influence. Furthermore, CRD does not mediate the relationship between the independent variables and equity valuation. The study highlights that equity value in Indonesia’s banking industry is primarily shaped by effective management of intellectual capital, rather than by dividend policy or CRD.